أثر استخدام استراتيجية التدريس للتفكير في تنمية مهارات فهم المقروء لدى طالبات المستوى الثاني من قسم الإعداد اللغوي بجامعة الراية - Tantrie Aryani Muflihat; Ade Sudiana (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2018)
The study aimed to investigate the effect of using a thinking strategy on the development of reading comprehension skills on second-semester female students of the language preparatory departement at STIBA Ar-Raayah. This study used an experimental research method. The research sample consisted of (30) female students from (86) population. The sample divide into two groups: experimental groups that consisted of (15) students and control groups that consisted of (15) students. It is was selected randomly to ensure equivalence between the two groups. The researcher used the percentage method to find out the differences between the two groups. And the following results were attaired the thinking strategy influences on the improvement of reading comprehension skills for the second-semester students of language preparatory departement at STIBA Ar-Raayah.The conclusion from the result was an effect of this teaching technique was effectif. So, the study has recommended for teachers to use the thinking strategy to develop the skills of reading comprehension among the the Non-Arabic speaking learners, especially students at the STIBA Ar-Raayah. Because the aplication of this strategy help students to develop of language in the daily and change the way of thinking.